Secondary desmoplastic fibroma-like tissue changes in mandibular fibrous dysplasia: clinicopathological and molecular study of a case. Issue 1 (January 2020) - Corsi, A.; Fadda, M.T.; Terenzi, V.; Valentini, V.; Riminucci, M.
Abstract: Fibrous dysplasia may show locally aggressive behaviour reflecting secondary intralesional changes, extension to soft tissue, or malignant transformation. We report the case of a patient with polyostotic fibrous dysplasia who had a giant mandibular lesion consisting of histologically typical, genotypically-confirmed, fibrous dysplasia merged with a fibrotic and hypocellular desmoplastic fibroma-like tissue in which the same Gsα-R201H mutation was detected. The occurrence of the same mutation in both the fibrous dysplasia and areas of desmoplastic fibroma suggests that the fibroma-like tissue reflects an unusual secondary tissue change within an otherwise typical fibrous dysplasia. To the best of our knowledge, only four cases of fibrous dysplasia with desmoplastic fibroma-like tissue changes have been reported.